Three essays in urban economics - MOURA, Klebson Humberto de Lucena (2018)
The objective of this thesis is to study some issues related to the Brazilian urban environment. In the first chapter the aim identify and to measure the external returns to human capital in Brazil using information from the Ministry of Labor’s Annual Social Information Report (RAIS) on all urban agglomeration in the country for the period 2002-2014. With a two step estimation and using instrumental variables for identification we find a considerable effect of local human capital concentration on local wages. The set of results indicates that, in the case of brazilian labor market areas, the external returns to human capital are a 0.86% increase in local wages for an increase of one percentage point in college graduates. Consistent with theoretical expectations and similar to literature results, we also found that the impact of local human capital is stronger for unskilled than for skilled workers. Finally, results are robust and not equally distributed across sectors; On the second chapter we analyze the influence of exposure to public spaces on victimization using a large nationally representative cross-section sample of Brazilian individuals for 2009, using propensity score matching techniques to create counterfactuals, performing robustness checks and implementing a simulation-based sensitivity analysis that support a causal interpretation of the results. We find that individuals with more than one hour of commuting have an overall 2.1% increase in the probability of being victim of robbery, with no robust impact on theft. Also, following the exposure literature we find larger effect on the probability of robbery victimization on women when compared with men, 2.5% and 2.2% respectively; Finally, in the last chapter, presents an evaluation of the impact of the housing financing for Brazilian families in commuting time. With the use of PNAD 2014 information and a strategy based on Propensity Score Matching and sensitivity analysis, the results indicate that housing financing increases the probability of the beneficiaries having larger commuting time. However, this effect is concentrated in lower income families living in non-metropolitan urban areas.